Microfluidic separation of the live and dead bacteria cells in the sensor of the bacteriological quality of water - Liew, Jun Bin. (2009)
There is a interest in developing the low cost microfluidic device for separation of live and dead bacterial cells which can be applied in sensor for bacteriology of water and wastewater quality. There are several researches have been done in this area and this report is mainly focus on two technologies, hydrophobic interaction chromatography and dielectrophoresis. The objective of this project is to investigate separation efficiency of hydrophobic chromatography separation and preparation of experiment set up for dielectrophoresis.